Preparação e caracterização de carvões ativados obtidos a partir de vagens de Flamboyant (Delonix regia) mediante ativação química com NaOH - Vargas, Alexandro Manolo de Matos (2010)
Activated carbons were prepared and characterized using flamboyant pods by chemical a, activation with NaOH under conditions of activation temperature of 700°C, activation time of 1.5 h and three different ratios NaOH/charcoal: 1:1 (CA-1), 2:1 (CA-2) and 3:1 (AC-3). The properties of these materials, including BET surface area, total pore volume, micropore volume, mesopore volume, pore diameter and pore size distribution were obtained from N2 adsorption and desorption isotherms. The activated carbons obtained were essentially microporous. Thermogravimetric analysis, Fourier transform infrared spectroscopy and solid state 13C nuclear magnetic resonance spectroscopy, allowed identify the lignocellulosic structure of the precursor and the presence of heteroaromatic groups on the surface of activated carbons. Scanning electron microscopy images showed a high pore development by the process. The process optimization of the best conditions of temperature, time and ratio NaOH/charcoal was performed using the response surface methodology. In this methodology, a central composite rotatable design of three factors and five levels was developed to know the optimum values of the responses; BET surface area and yield. Statistical analysis showed that the ratio NaOH/charcoal and temperature are the factors that most affect the responses mentioned above. The best conditions of temperature (761.70°C), time (0.86h) and ratio NaOH/charcoal (3.46:1), showed a BET surface area of 2854 m² g-1 and yield of 10.8%. The results indicated the potential use of flamboyant pods as a precursor material in the preparation of low-cost activated carbon.